Molecular confirmation of Lassa fever imported into Ghana - Joseph H.K. Bonney; Edward O. Nyarko; Sally-Ann Ohene; Joseph Amankwa; Ralph K. Ametepi; Shirley C. Nimo-Paintsil; Badu Sarkodie; Prince Agbenohevi; Michael Adjabeng; Nicholas N.A. Kyei; Samuel Bel-Nono; William K. Ampofo (African Journal of Laboratory Medicine, 2016)
Background: Recent reports have shown an expansion of Lassa virus from the area where it was first isolated in Nigeria to other areas of West Africa. Two Ghanaian soldiers on a United Nations peacekeeping mission in Liberia were taken ill with viral haemorrhagic fever syndrome following the death of a sick colleague and were referred to a military hospital in Accra, Ghana, in May 2013. Blood samples from the soldiers and five asymptomatic close contacts were subjected to laboratory investigations. Objective: We report the results of these investigations to highlight the importance of molecular diagnostic applications and the need for heightened awareness about Lassa fever in West Africa.